SYSTEMS FOR MONITORING AND RECORDING PROCESSES IN LOGISTIC OPERATORS OF ELECTRONIC COMMUNICATIONS NETWORKS (Natural Resources and Technology, 2016)
Repeatedly pronounced complexity of the environment in whichcompanies operate today’s ever increasing uncertainty in operation, imposesthe necessity of numerous materials. Decision-making process in theseconditions is no longer a simple and routine work.Considering the main objective of enterprise - profit, which only possiblethrough meeting the needs of consumers as soon as possible. Most businessdecisions for field operations at a telecommunications company are taken inorder to establish harmony between the potential of the company and the scopeof tasks to be completed in the field (application for defects network connectionsand new installations, etc.). These decisions can generally have a marketing orfinancial dimension. The quality of decisions largely depends on the qualityof information that managers have decision-making. In fact, the reduction ofuncertainty in decision making is directly related and proportionate to havingquality, accurate and timely information.The company must constantly has adequate information on the locationand movement of vehicles in order to making quality decisions for the optimalutilization of the vehicles available.